Perceptions of candidate spouses in the 2012 presidential election: the role of gender, race, religion, and partisanship. (2nd January 2019) - Elder, Laurel; Frederick, Brian
ABSTRACT: The wives, and more recently, the husbands, of presidential candidates have taken on vital roles in campaigns, acting as surrogates for their partners, mobilizing voters, fundraising, and making high-profile speeches as well as appeals to targeted groups of voters. Despite their importance, presidential candidate spouses represent an under-investigated set of political actors. This project draws on American National Election Study data to analyze public perceptions of the 2012 presidential candidate spouses, Michelle Obama and Ann Romney, and explore how these perceptions compare to attitudes about previous presidential candidate spouses going back to 1992. Since these two spouses represent historic firsts, with Michelle Obama the first Black presidential candidate spouse and Ann Romney the first Mormon presidential candidate spouse, our analysis pays particular attention to the role of gender, race, and religion in public evaluations of these two women. This study also explores how and why candidate spouses are able to remain quite popular even in today's highly partisan environment. Our results provide insights into key areas of stability and change in the public's views and expectations for would-be first ladies.